Women’s Legal Rights over 50 Years : What Is the Impact of Reform? - Hallward-Driemeier, Mary (World Bank, Washington, D.C., 2013)
This study uses a newly compiled database of women's property rights and legal capacity covering 100 countries over 50 years to test for the impact of legal reforms on employment, health, and education outcomes for women and girls. The database demonstrates gender gaps in the ability to access and own property, sign legal documents in one's own name, and have equality or non-discrimination as a guiding principle of the country's constitution. In the initial period, 75 countries had gender gaps in at least one of these areas and often multiple ones. By 2010, 57 countries had made reforms that strengthened women's economic rights, including 28 countries that had eliminated all of the constraints monitored here. In the cross-section and within countries over time, the removal of gender gaps in rights is associated with greater participation of women in the labor force, greater movement out of agricultural employment, higher rates of women in wage employment, lower adolescent fertility, lower maternal and infant mortality, and higher female educational enrollment. This paper provides evidence on how the strengthening of women's legal rights is associated with important development outcomes.